49 Performance, Carcass Characteristics, and Meat Quality of Kiko Wethers Finished on Pasture and Browse. - Karki, U (J Anim Sci, 2018)
Raising goats on pastures and other grazing systems for low-input costs is gaining popularity among producers. However, their performance on different grazing systems, and the resulting carcass and meat quality is not much reported. The objective of the study was to evaluate the performance, carcass, and meat quality of Kiko wethers finished on pastures and browse. Eleven Kiko wethers were raised on year-round grazing systems from April 2015 to November 2017. Grazing lands consisted of southern pine silvopastures planted with cool- and warm-season forages, woodlands, and a system containing planted forages and browse. Wethers were rotationally stocked in these systems based on the available forages. Animal performance data (body weight, FAMACHA, body condition score) were collected in every two weeks. At the end of the grazing study, wethers were slaughtered, and carcass and meat quality data were collected. Animal performance data were analyzed in SAS 9.4 using MANOVA procedure, and descriptive statistics were calculated for carcass and meat quality. Animals gained 50 kg (±2.1 SE) body weight during the study period showing a significant polynomial trendline of body weight with age (R(2) = 0.98). Animals showed comparatively higher FAMACHA score and lower body condition score during the first five months of grazing. FAMACHA score ranged from 1.5 to 3.1 and body condition score from 1.8 to 2.8 during the study period. Body weight, FAMACHA score, and body condition score were highly correlated (p<0.0001). Median values for dressing percent, hot-carcass pH, cold-carcass pH, protein content, and crude fat content were 50.84%, 6.66, 5.67, 23.26%, and 3.95% respectively. Results showed that it is quite feasible to raise goats on forages and browse when there are enough grazing lands and suitable environmental conditions for growing forages and browse to obtain quality meat products.